Ca‐channel blocker‐induced gingival overgrowth that improved with non‐surgical therapy during visiting care: a case report. (23rd July 2015) - Kato, Tomotaka; Takiuchi, Hiroya; Yamaguchi, Masahiro; Naito, Toru
Abstract : Objectives: To present a case of gingival overgrowth during visiting care. Background: Ca‐channel blocker‐induced gingival overgrowth is a well‐known adverse event. However, only limited information on the treatment of calcium‐channel blocker‐induced gingival overgrowth during visiting care has been reported. Clinical report: The patient was an 88‐year‐old female living in a nursing home since dementia. She had been taking a calcium‐channel blocker and observed gingival overgrowth. Initial therapy was performed and changed the antihypertensive medication from a calcium‐channel blocker to an angiotensin converting enzyme inhibitor. After initial therapy, the gingival overgrowth improved significantly. In addition, the defecation rate was improved. Conclusion: This case indicated that periodontal therapy is useful even for dementia patients during visiting dental care.